Odorant Receptor 51E2 Agonist β-ionone Regulates RPE Cell Migration and Proliferation - Jovancevic, Nikolina; Khalfaoui, Soumaya; Weinrich, Markus; Weidinger, Daniel; Simon, Annika; Kalbe, Benjamin; Kernt, Marcus; Kampik, Anselm; Gisselmann, Günter; Gelis, Lian; Hatt, Hanns (Frontiers in Physiology, 2017)
The odorant receptor 51E2 (OR51E2), which is well-characterized in prostate cancer cells and epidermal pigment cells, was identified for the first time as the most highly expressed OR in human fetal and adult retinal pigment epithelial (RPE) cells. Immunofluorescence staining and Western blot analysis revealed OR51E2 localization throughout the cytosol and in the plasma membrane. Additionally, immunohistochemical staining of diverse layers of the eye showed that the expression of OR51E2 is restricted to the pigment cells of the RPE and choroid. The results of Ca2+-imaging experiments demonstrate that activation of OR51E2 triggers a Ca2+ dependent signal pathway in RPE cells. Downstream signaling of OR51E2 involves the activation of adenylyl cyclase, ERK1/2 and AKT. The activity of these protein kinases likely accounts for the demonstrated increase in the migration and proliferation of RPE cells upon stimulation with the OR51E2 ligand β-ionone. These findings suggest that OR51E2 is involved in the regulation of RPE cell growth. Thus, OR51E2 represents a potential target for the treatment of proliferative disorders.